Plant polyphenols as green sunscreen ingredients: A systematic review - Ng, Shin Yi; Vicit Rial, Eh Su; Gew, Lai Ti * (Wiley, 2022)
Background: Excessive exposure to ultraviolet radiation has harmful effects on human skin. At present, synthetic and mineral types of sunscreens used to protect against these harmful damages have been reported to cause negative health and environmental effects. The studies involving characterization and isolation of phytoconstituents from natural botanical sources are important to discover their potential beneficial effects on sunscreen development AIM: This systematic review provides specific and compiled information on the photoprotective properties of natural botanical sources for sunscreen development. The efforts in research and innovation are essential to ensure the safety and sustainability of plant-based sunscreen products.